2016
DOI: 10.1155/2016/8716016
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mRNA Expression of eEF1A Isoforms and a PI3K/Akt/mTOR Pathway in a Cellular Model of Parkinson’s Disease

Abstract: The PI3K/Akt/mTOR pathway is one of dysregulated pathways in Parkinson's disease (PD). Previous studies in nonneuronal cells showed that Akt regulation can be increased by eukaryotic protein elongation factor 1 alpha 2 (eEF1A2). eEF1A2 is proposed to contribute protection against apoptotic death, likely through activation of the PI3K/Akt pathway. Whether eEF1A2 plays a role in the prevention of cell death in PD has not been investigated. Recently, gene profiling on dopaminergic neurons from postmortem PD patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 48 publications
3
31
0
Order By: Relevance
“…PI3K-AKT activation is associated with neuronal activities, including proliferation, apoptosis, differentiation and metabolism (33). PI3K-AKT dysregulation is critical in the development of CNS diseases, including Parkinson's Disease, ischemic brain injury and epilepsy (34)(35)(36). In the present study it was demonstrated that p-AKT expression decreased significantly in astrocytes in an epileptic environment.…”
Section: Discussionsupporting
confidence: 53%
“…PI3K-AKT activation is associated with neuronal activities, including proliferation, apoptosis, differentiation and metabolism (33). PI3K-AKT dysregulation is critical in the development of CNS diseases, including Parkinson's Disease, ischemic brain injury and epilepsy (34)(35)(36). In the present study it was demonstrated that p-AKT expression decreased significantly in astrocytes in an epileptic environment.…”
Section: Discussionsupporting
confidence: 53%
“…Dopaminergic degeneration is still a mystery for scientists. Many researchers directed the investigations towards pathogenesis, [46][47][48] epidemiology, pathology, and genetics. While major research signs of progress have been made, as well as the current recognizable proof of conceivable environmental and genetic risk factors for PD, further molecular docking studies are performed to detect the molecular interactions, active site prediction, and drug interaction based studies and cellular pathway research is necessary to explicate the root causes of PD and to discover enhanced treatments.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 Many shreds of evidence suggest that phosphatidylinositol-3 kinase (PI3K)/Akt (protein kinase-B)/mammalian target of the rapamycin (mTOR) pathway (PI3K/Akt/mTOR) pathway signaling related to dopaminergic neuron degeneration in PD. [46][47][48] The neuron degeneration concurrently influences the wider region of the brain responsible for dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous studies reported that the eEF1A declined in the human brain tissues with history of PD disease progression, indicating an association of eEF1A and altered polypeptide synthesis in the corresponding area (Licker et al, 2014;Garcia-Esparcia et al, 2015). In the cellular model, upregulation of genes of eEF1A has been found to be associated with the increased expression of PI3K, AKT, and mTOR in 1methyl-4-phenylpyridinium (MPP+)-induced cellular PD model (Khwanraj et al, 2016). Since the roles of eEF1A1 and eEF1A2 in the prevention of DA neuronal cell death in PD remain unclear, this study aims to investigate the role of eEF1A isoforms on degenerated DA neurons by using Caenorhabditis elegans as a PD model.…”
Section: Introductionmentioning
confidence: 95%
“…Having revealed a role for eEF1A in PI3K/AKT/mTOR mechanism in several cellular models (Amiri et al, 2006;Khwanraj et al, 2016), we sought to examine whether the eft-3 and eft-4 mediate neuroprotection through the cell survival signaling, PI3K/AKT/mTOR, in 6-OHDA-induced C. elegans PD model. We performed real-time qPCR to analyze the mRNA levels of daf-2, age-1, let-363, pdk-1, akt-1, and akt-2, which are homologs with cell-survival signaling genes in mammals.…”
Section: Decreasing Of Eft-3 or Eft-4 Affected The Survival Gene Exprmentioning
confidence: 99%